An integration of grounded theory and chance discovery to explore the technology opportunity. (1st January 2012) - Chiu, Tzu-Fu
To explore the technology opportunity is an important task for managers and stakeholders to grasp the emerging trends of their industries. Solar cell, one of green energies, is growing at a fast pace with its clean and renewable characters. In addition, the patent data contains plentiful technological information from which it is worthwhile to extract further knowledge. Therefore, an integrated approach of grounded theory and chance discovery has been proposed in order to analyse the patent data and to explore the technology opportunity. Grounded theory is employed to provide a procedural basis for guiding the research processes, while chance discovery is adopted to provide the mining techniques for discovering the relations within the textual data. Consequently, the relation types were recognised, the tendency of solar cell technology was identified, and the active companies and significant technical subcategories in the solar cell industry were also observed.